Step
*
1
1
of Lemma
reg-seq-inv_wf
1. b : ℕ+
2. x : ℕ+ ⟶ ℤ
3. b-regular-seq(x)
4. k : ℕ+
5. ∀m:ℕ+. ((2 * m) ≤ (k * |x m|))
6. ∀m:ℕ+. (¬((x m) = 0 ∈ ℤ))
7. reg-seq-inv(x) ∈ ℕ+ ⟶ ℤ
8. n : ℕ+
9. m : ℕ+
10. 0 < |x n|
11. 0 < |x m|
⊢ |(((x n) * (x m)) * m * (reg-seq-inv(x) n)) - ((x n) * (x m)) * n * (reg-seq-inv(x) m)| ≤ (|(x n) * (x m)|
  * (2 * b * ((k * k) + 1))
  * (n + m))
BY
{ ((Subst' ((x n) * (x m)) * m * (reg-seq-inv(x) n) ~ (x m) * m * (x n) * (reg-seq-inv(x) n) 0 THENA Auto)
   THEN (Subst' ((x n) * (x m)) * n * (reg-seq-inv(x) m) ~ (x n) * n * (x m) * (reg-seq-inv(x) m) 0 THENA Auto)
   THEN RepUR ``reg-seq-inv`` 0⋅
   THEN (RWO "div_rem_sum2" 0 THENA Auto)
   THEN (GenConcl ⌜(4 * n * n rem x n) = r1 ∈ {r:ℤ| |r| < |x n|} ⌝⋅ THENA Auto)⋅
   THEN (GenConcl ⌜(4 * m * m rem x m) = r2 ∈ {r:ℤ| |r| < |x m|} ⌝⋅ THENA Auto)⋅) }
1
1. b : ℕ+
2. x : ℕ+ ⟶ ℤ
3. b-regular-seq(x)
4. k : ℕ+
5. ∀m:ℕ+. ((2 * m) ≤ (k * |x m|))
6. ∀m:ℕ+. (¬((x m) = 0 ∈ ℤ))
7. reg-seq-inv(x) ∈ ℕ+ ⟶ ℤ
8. n : ℕ+
9. m : ℕ+
10. 0 < |x n|
11. 0 < |x m|
12. r1 : {r:ℤ| |r| < |x n|} 
13. (4 * n * n rem x n) = r1 ∈ {r:ℤ| |r| < |x n|} 
14. r2 : {r:ℤ| |r| < |x m|} 
15. (4 * m * m rem x m) = r2 ∈ {r:ℤ| |r| < |x m|} 
⊢ |((x m) * m * ((4 * n * n) - r1)) - (x n) * n * ((4 * m * m) - r2)| ≤ (|(x n) * (x m)|
  * (2 * b * ((k * k) + 1))
  * (n + m))
Latex:
Latex:
1.  b  :  \mBbbN{}\msupplus{}
2.  x  :  \mBbbN{}\msupplus{}  {}\mrightarrow{}  \mBbbZ{}
3.  b-regular-seq(x)
4.  k  :  \mBbbN{}\msupplus{}
5.  \mforall{}m:\mBbbN{}\msupplus{}.  ((2  *  m)  \mleq{}  (k  *  |x  m|))
6.  \mforall{}m:\mBbbN{}\msupplus{}.  (\mneg{}((x  m)  =  0))
7.  reg-seq-inv(x)  \mmember{}  \mBbbN{}\msupplus{}  {}\mrightarrow{}  \mBbbZ{}
8.  n  :  \mBbbN{}\msupplus{}
9.  m  :  \mBbbN{}\msupplus{}
10.  0  <  |x  n|
11.  0  <  |x  m|
\mvdash{}  |(((x  n)  *  (x  m))  *  m  *  (reg-seq-inv(x)  n))  -  ((x  n)  *  (x  m))  *  n  *  (reg-seq-inv(x)  m)|  \mleq{}  (|(x  n)
                                                                                                                                                                                          *  (x 
                                                                                                                                                                                                m)|
    *  (2  *  b  *  ((k  *  k)  +  1))
    *  (n  +  m))
By
Latex:
((Subst'  ((x  n)  *  (x  m))  *  m  *  (reg-seq-inv(x)  n)  \msim{}  (x  m)  *  m  *  (x  n)  *  (reg-seq-inv(x)  n)  0
    THENA  Auto
    )
  THEN  (Subst'  ((x  n)  *  (x  m))  *  n  *  (reg-seq-inv(x)  m)  \msim{}  (x  n)  *  n  *  (x  m)  *  (reg-seq-inv(x)  m)  0
              THENA  Auto
              )
  THEN  RepUR  ``reg-seq-inv``  0\mcdot{}
  THEN  (RWO  "div\_rem\_sum2"  0  THENA  Auto)
  THEN  (GenConcl  \mkleeneopen{}(4  *  n  *  n  rem  x  n)  =  r1\mkleeneclose{}\mcdot{}  THENA  Auto)\mcdot{}
  THEN  (GenConcl  \mkleeneopen{}(4  *  m  *  m  rem  x  m)  =  r2\mkleeneclose{}\mcdot{}  THENA  Auto)\mcdot{})
Home
Index